Օրագրերի ենթաժանրը 19-րդ դարի Իրանի մեմուարային գրականության մեջ - Արմինե Մարտիրոսյան (ՀՀ ԳԱԱ հրատ.)
The article discusses several travel diaries written by Persian travelers during their trips to Russia and European countries. In these works keeps up developing a relatively new subgenre of blogs, which in the early XIX century got its second life. Here there are considered the reasons and preconditions for the emergence and the writing o f "travel diaries", as well as their main features and ways of forming the traditions of Persian memoirs.
Keywords: Language and Literature